Therapeutic potential of flavonoids used in traditional Chinese medicine - a comparative study of galangin, kaempferol, chrysin and fisetin - Arkadiusz Sokal; Klaudia Stocerz; Paweł Olczyk; Monika Kadela-Tomanek (Śląski Uniwersytet Medyczny w Katowicach, 2024)
One of the branches of traditional Chinese medicine (TCM) is herbal medicine. In this paper, we focus on the biological activity of substances belonging to flavonoids and specific examples of their impact on various body systems. Flavonoids are a group of chemical compounds included in plant materials, honey, propolis or mushrooms used in TCM. Chrysin, galangin, kaempferol and fisetin are examples of flavonoids showing, among others, antioxidant, anti-inflammatory or antibacterial properties, which are the subject of various scientific studies aimed at examining their potential therapeutic effect.